Anticoagulation in CRRT: Agents and strategies in Australian ICUs - Davies, Hugh; Leslie, Gavin (Elsevier, 2007)
Background: Continuous Renal Replacement Therapy (CRRT) should ideally operate with as little interruption as possible. The majority of circuit terminations occur due to clotting. The longevity of CRRT is able to be improved when the extracorporeal circuit is anticoagulated. Aims: This article will focus attention on anticoagulant agents used in Australian intensive care units (ICU) to prevent clotting in the CRRT circuit. Discussion: Anticoagulants reviewed include unfractionated or standard heparin, regional heparinisation, low-molecular weight heparins and heparinoids, regional citrate, platelet-inhibiting agents (prostacyclin), thrombin antagonists (recombinant hirudin) and therapy with no anticoagulant use. Each type of anticoagulant was reviewed for mode of action, the method of delivery and how the effect is monitored. Circuit life and the incidence of bleeding were considered as the principle end points in selecting therapy, as well as side-effects with administration such as metabolic disturbances, contraindications to use including allergy and ease of use in the clinical environment. Conclusion: No approach to anticoagulation has yet been reported to be as successful in extending circuit life, whilst remaining inexpensive, easy to manage and easy to reverse, as unfractionated heparin. Certain patient conditions may preclude the use of heparin, such as heparin-induced thrombocytopenia (HIT); then heparinoids, thrombin antagonists and sodium citrate are suggested as alternatives. Regional citrate reduces haemorrhagic complications in patients who have coagulation disorders or are at risk of bleeding. Clinical experience with various agents and strategies should also influence choice. The option of no anticoagulant may be appropriate in selected patients rather than more expensive and less familiar drugs. © 2006 Australian College of Critical Care Nurses Ltd. Published by Elsevier Australia (a division of Reed International Books Australia Pty Ltd). All rights reserved.